1999
DOI: 10.1101/gad.13.13.1678
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an SCF ubiquitin-ligase complex required for auxin response in Arabidopsis thaliana

Abstract: The plant hormone auxin regulates diverse aspects of plant growth and development. We report that in Arabidopsis, auxin response is dependent on a ubiquitin-ligase (E3) complex called SCF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
497
0
8

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(526 citation statements)
references
References 56 publications
21
497
0
8
Order By: Relevance
“…Generally, F-box proteins interact with the CUL1 -RBX1 subcomplex through the ASK1 or ASK2 proteins. TIR1 immunoprecipitates with CUL1, ASK1 and RBX1, indicating that these subunits form an SCF TIR1 complex [15,17]. In line with this, the tir1, ask1 and axr6 mutants are resistant to auxin [15,18].…”
Section: Auxin Modulates Gene Transcriptionmentioning
confidence: 70%
See 1 more Smart Citation
“…Generally, F-box proteins interact with the CUL1 -RBX1 subcomplex through the ASK1 or ASK2 proteins. TIR1 immunoprecipitates with CUL1, ASK1 and RBX1, indicating that these subunits form an SCF TIR1 complex [15,17]. In line with this, the tir1, ask1 and axr6 mutants are resistant to auxin [15,18].…”
Section: Auxin Modulates Gene Transcriptionmentioning
confidence: 70%
“…Auxin signaling is mediated through the ubiquitinproteasome pathway In Arabidopsis, the characterization of the auxin resistant mutants axr1 and tir1 led to the discovery that the ubiquitin-proteasome pathway is involved in auxin response [12,14,15]. Ubiquitin-mediated protein degradation has emerged as a vital process that regulates the growth and development of eukaryotic organisms.…”
Section: Auxin Modulates Gene Transcriptionmentioning
confidence: 99%
“…We carried out immunoprecipitation assays as described 28 using A. thaliana protein extracts prepared from 12-d-old to 14-d-old seedlings grown under long-day photoperiod conditions in solid nutrient medium. We prepared extracts by homogenizing seedlings in ice-cold buffer containing 50 mM Tris Cl, 150 mM NaCl, 0.5% Nonidet P-40, 1 mM phenylmethylsulfonyl fluoride and 1× protease inhibitor cocktail.…”
Section: Methodsmentioning
confidence: 99%
“…Recent genetic and biochemical analyses have suggested that ubiquitin-related proteolysis is central to several aspects of auxin response (Gray et al, 1999(Gray et al, , 2001Dharmasiri and Estelle, 2002;Kepinski and Leyser, 2002;Leyser, 2002). As a model system, some advances in how auxin promotes lateral root formation have been reported recently (Xie et al, 2000;Casimiro et al, 2001;Xie et al, 2002).…”
Section: Introductionmentioning
confidence: 99%